4 Clinical implementation of a dedicated brain treatment planning optimizer for stereotactic treatments: A new treatment paradigm. (December 2018) - Gevaert, T.; Girardi, A.; Engels, B.; Coussement, G.; Boussaer, M.; De Ridder, M.
Abstract : Introduction: Clinical implementation of a novel dedicated and automated treatment-planning solution for cranial indications, Elements. Single lesions can be targeted with an inversely optimized VMAT approach using automated arc trajectory optimization (Cranial SRS Element) while up to fifteen metastatic brain tumors can be automatically targeted with a single isocenter and multiple inversely-optimized dynamic conformal arcs (Multiple Brain Mets SRS Element). Material and Methods: The very first 15 treated patients were analyzed, each representing a variable number of lesions (1–12). Depending on the number and location of the lesions a dedicated Element was selected and used in order to achieve the specific planning constraints. The plans were evaluated by means of Paddick conformity (CI) and gradient index (GI). Patient specific quality assurance (QA) was performed with gafchromic EBT3 film and portal imager. Results: The Elements software tools generated plans with CI of 0.71 ± 0.09 and a gradient index of 3.9 ± 1.4. All plans achieved the organ at risk constraints. A gamma of 3%/3 mm was used for the QA. A 98 % and 98, 2 % passing rate was found for the EBT3 film and portal imager, respectively. This shows also the good concordance between film and EPID, suggesting that patient specific QA can be perform with the portal imager rather than the time consuming films. Conclusions: The automated dose planning Elements revive dynamic conformal arcs as the paradigm for linac-based stereotactic radiosurgery of multiple brain metastases and at the same time implements an improved VMAT approach for single lesions with the use of automated arc trajectory optimization. This study shows the implementation of this technique in the routine clinical environment with an improved planning and treatment efficiency.